Characteristics of Middle-Lower Ordovician Ultradeeply Buried Carbonate Reservoirs in Shunbei Area, Tarim Basin—A Case Study from Well SHBP1. (15th March 2022) - Chongyang, Xiao; Rui, Zhao; Heng, Fu; Cheng, Huang; Jun, Han; bo, Lin
Abstract : Fracture-pore complexes, located at fault zones of Darriwilian carbonates, are the main exploration targets in the Shunbei area, Tarim Basin. This article focuses on the carbonate characteristics in the Lower Ordovician of Well ShunbeiPeng1 (SHBP1), the carbonate is sandwiched by two trending NW-SE deep-seated, strike-slip faults in the Shuntuoguole uplift. Based on detailed core investigation and careful petrographic examination, two main reservoir types, denoting microquartz and dolomite, are recognized. The former is mainly constrained in the lower part of the sampled core and gradually evolves to the latter with progressively decreases of silica. Integrated isotopic geochemistry (C, O, and Sr) and fluid inclusion microthermometry suggest that the fluids are hydrothermal origin and migrate along deep-seated strike-slip faults, forming favorable carbonate reservoirs. The fault-controlled hydrothermal reservoirs, characterized by the strong amplitude in the seismic profile, would be the most promising exploration area in deeply buried carbonates in the Tarim Basin, particularly in the Shuntuoguole area.